Psychological Experiences and Coping Behaviors of Children Living on Streets: An Interpretative Phenomenological Analysis - Yousaf, Kainaat; Rafique, Rafia (Applied Psychology Review, 2025)
The qualitative research explored the experiences of children aged 6–12 living on the street, investigated their experiences, and examined their coping behaviors. A volunteer sample of six participants was recruited using purposive sampling, including three male and three female participants who had been living on the street for more than a year. In-depth interviews were conducted with the respondents. An interpretative phenomenological approach by Smith and Osborn (2014) was used to analyze the data. The IPA resulted in four superordinate themes, twenty-three subordinate themes, and eighty-two individual themes. The superordinate themes included social and environmental experiences, psychological experiences, acting out and overt behaviors, and coping styles. The study has significant applications in the fields of social psychology and community psychology by shedding light on the experiences of children in overcoming challenges and establishing strategies that foster the enhancement of adaptive coping among children living on the streets. Moreover, it encourages the design of community-based programs to enhance the well-being of children by addressing the adversities they face.